Magnetic and antibacterial studies of sol-gel dip coated Ce doped TiO2 thin films: Influence of Ce contents. Issue 1 (January 2020) - Kayani, Zohra Nazir; Maria; Riaz, Saira; Naseem, Shahzad
Abstract: Ce-doped TiO2 thin films were synthesized by sol-gel dip coating route to evaluate the effect of Ce doping percentage on properties of TiO2 . X-ray diffraction spectra revealed both anatase and brookite phases, and Ce doping favours the anatase–brookite transformation of TiO2 films. The optical constants of the thin films were achieved by evaluating spectroscopic UV-VIS-NIR spectrophotometry data. The band gap of the Ce doped TiO2 was reduced from ~3.93 eV to ~3.79 eV with an increase in Ce doping percentage. All films have shown ferromagnetic behaviors which increase with the increase in Ce content due to enhancement in the bound magnetic polaron. Higher Ce doping increases the oxygen vacancies and saturation magnetization. Boost magnetic properties stem from the generation of the interaction between the Ce ion and an oxygen vacancy. The study showed that the antimicrobial activity of Ce doped TiO2 is ineffective. Hence doping of Ce can modify the properties of TiO2 and are used in LEDs, magneto-optical devices and solar cells.